El ejercicio físico y deportes para mejorar la calidad de vida del adulto mayor - Arellano Arevalo, Karina Magaly (2021)
The biggest adult people present a series of biological, psychological and social changes so that understanding these changes facilitates the study of the declining of their functional capacity and the reduction of resistance to stress and disease. The present study has the purpose of analyzing the incidence of a physical exercise program and sports to improve the quality of life of the major adult in the geriatric center of the city of Quevedo, province of Los Ríos, the methodology employed was a descriptive cross-sectional design. quantitative, the study set was 80 people from the third age between 65 and 86 years of age, in the probabilistic intentional where the adults participate who have autonomy in their daily performance. within the theoretical methods employed, synthetic analytical, deductive inductive and empirical methods the method of measurement and the instrument of collection of the results is applied, the life quality questionnaire associated with the physical activity, the bold results from the major adults perform a lot of the programmed physical exercise, plus these are type 1 obesity, 80% of the subjects are there and they are successful in carrying out programmed physical exercises with the participation of a specialist and the programmed physical exercise guide proposes an alternative course solution to the problem encountered in terms of its structure and possibilities of execution.